Innate immune regulation and cancer immunotherapy - Wang, Rongfu (Springer New York, 2012)
There has been major growth in understanding innate immune signaling, inflammation, immune suppression and cancer immunotherapy. Innate immune regulation and cancer immunotherapy highlights emerging research about the underlying mechanisms of innate immunity and signaling regulation, inflammation and immune suppression that promote or inhibit cancer development and progression, and offers novel ideas and strategies to develop therapeutic cancer drugs or cell therapy by manipulating or blocking these negative signaling pathways and generating potent antitumor immunity.  Recent studies have identified key innate immune receptors or sensors, novel signaling molecules and immune regulatory molecules that control immune responses, inflammation and immune suppression in cancer and other diseases. Major progresses in understanding of tumor antigens, immune suppressive molecules and cell population and novel vaccine strategies bring therapeutic cancer vaccines and drugs in realty.  With chapters written by internationally recognized contributors, this book provides essential introduction and guide for immunologists, basic, translational and clinical cancer researchers. Features of this book: Offers the most recent development from basic science to clinical application of cancer immunotherapy, thus serving useful guide for immunologists, and cancer researcher and oncologists. Identify key immune signaling molecules and cell populations that dampen immune responses against cancer, thus providing novel strategies to develop therapeutic cancer vaccines and drugs.